ASSESSMENT OF BIOLOGY AND MORPHOMETRIC PARAMETERS OF JATROPHA LEAF WEBBER AND FRUIT BORER, PEMPELIA MOROSALIS FAB. - VEERESHKUMAR; KUMAR, C. T. ASHOK; PRASAD, B. S. RAJENDRA; S. C.TOPAGI; CHOWDARY, RAJESH; B. ARUNKUMAR (The Bioscan, 2013)
Jatropha is an important bio-fuel crop. The plant suffers more from several insect pests damage. Of which, Pempelia morosalis Fab. caused serious damage. Studies on the assessment of biology and morphometric parameters of P. morosalis was carried out during 2011-12 at University of Agricultural Sciences, GKVK, Bangalore. The incubation period lasts for 5.9 ± 0.80 days. The duration of first, second, third, fourth and fifth instars were 2.3 ± 0.48, 4.2 ± 0.91, 5.8 ±0.78, 6.9 ± 0.87 and 8.1 ± 0.87 days, respectively; pupal period lasted for 6.9 ± 0.73 days. Male and female had longevity of 5.6 ± 0.5 and 7.5 ± 0.5 days, respectively, with fecundity of 66.5 ± 17.8 per female.